I thought of having understood. I tried but finally not succeeded.
And I didn't find how to add the opposite of cubes.
Exercise too much difficult for me.
O.K. Let's start with the Riemann sum for
\(\displaystyle \int_1^T\, f(t) dt\)[/tex]
where
f(t) = \(\displaystyle \frac{1}{t^3}\)
We choose the number of intervals N and let
\(\displaystyle \Delta\, =\, \frac{T-1}{N}\)
and we can write the Riemann sum as
R(T;N) = \(\displaystyle \Sigma_{k=0}^{k=N}\, \frac{1}{[1\, +\, k \Delta]^3} \Delta\)
Now substitute for \(\displaystyle \Delta\) to get
R(T;N) = \(\displaystyle \Sigma_{k=0}^{k=N}\, \frac{1}{[1\, +\, k \frac{T-1}{N}]^3} \frac{T-1}{N}\)
= \(\displaystyle \Sigma_{k=0}^{k=N}\, \frac{N^3}{[N\, +\, k (T-1)]^3} \frac{T-1}{N}\)
= \(\displaystyle \Sigma_{k=0}^{k=N}\, \frac{(T-1)\, N^2}{[N\, +\, k (T-1)]^3}\)
= (T-1) N
2 \(\displaystyle \left[\frac{1}{[N]^3}\, + \frac{1}{[N\, + (T-1)]^3}\, + \frac{1}{[N + 2 (T-1)]^3}\, \frac{1}{[N + 3 (T-1)]^3}\, +\, ...\, \frac{1}{[N + N (T-1)]^3}\right]\)
= (T-1) N
2 \(\displaystyle \left[\frac{1}{[N]^3} + \frac{1}{[N + (T-1)]^3}\, + \frac{1}{[N + 2 (T-1)]^3}\, \frac{1}{[N + 3 (T-1)]^3} +\, ...\, + \frac{1}{[N\, T]^3}\right]\)
= (T-1) N
2 \(\displaystyle \frac{T-1}{N}\) + \(\displaystyle \left[\frac{1}{[N + (T-1)]^3}\, + \frac{1}{[N + 2 (T-1)]^3}\, \frac{1}{[N + 3 (T-1)]^3} +\, ...\, + \frac{1}{[N\, T]^3}\right]\)
Now as N goes to infinity, we can drop that first term since it will go to zero, let a=T-1 and we could write
\(\displaystyle \int_1^T\, f(t) dt\)
= \(\displaystyle \lim_{N \to \infty} a N^2\left[\frac{1}{[N + a]^3}\, + \frac{1}{[N + 2 a]^3}\, \frac{1}{[N + 3a]^3} +\, ...\, + \frac{1}{[(a+1)N]^3}\right]\)
What does a have to be to almost match your expression of
\(\displaystyle \lim_{x \to \infty}x^2\left[\frac{1}{[x + 1]^3}\, + \frac{1}{[x + 2]^3}\, \frac{1}{[x + 3]^3} +\, ...\, + \frac{1}{[2\, x]^3}\right]\)
and what do you have to do [multiply by something, add something, ...] to R(T;N) to make it the same?